2015
DOI: 10.1176/appi.ps.201400405
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Burden Among Relatives of Persons With Schizophrenia: Results From the Swedish COAST Study

Abstract: Stigma had an impact on quality of life at the personal and family levels, and this was associated with overall burden. Increased awareness among service providers may decrease the impact of stigma on relatives, but associations need to be examined in larger studies in diverse cultures and treatment settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…A certain number of family members reported they were stigmatized by the public, and prejudice, blame, avoidance, rejection, and discrimination were directed towards them (Angermeyer et al 2003;Corrigan & Miller 2004;Dinos et al 2004;Grover et al, 2017;Perlick et al, 2007;Phelan et al 1998;Struening et al 2001). Stigma experienced by family members leads to an array of negative consequences, including withdrawal from social relationships, low self-esteem, reduced quality of life, long-term stress and burden, and so on (Allerby et al, 2015;Angermeyer et al 2003;O'Grady 2004;Perlick et al, 2007;Zhang et al, 2018). Hence, it is essential for mental health professionals to better understand this phenomenon, especially from the perspectives of family members themselves, to help families alleviate the harmful impacts of stigma.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…A certain number of family members reported they were stigmatized by the public, and prejudice, blame, avoidance, rejection, and discrimination were directed towards them (Angermeyer et al 2003;Corrigan & Miller 2004;Dinos et al 2004;Grover et al, 2017;Perlick et al, 2007;Phelan et al 1998;Struening et al 2001). Stigma experienced by family members leads to an array of negative consequences, including withdrawal from social relationships, low self-esteem, reduced quality of life, long-term stress and burden, and so on (Allerby et al, 2015;Angermeyer et al 2003;O'Grady 2004;Perlick et al, 2007;Zhang et al, 2018). Hence, it is essential for mental health professionals to better understand this phenomenon, especially from the perspectives of family members themselves, to help families alleviate the harmful impacts of stigma.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Psychiatric diagnoses, especially psychosis and schizophrenia, already carry tremendous stigma [ 5 , 6 ], which exists even on digital platforms like Twitter [ 7 ]. Although there are limited data on smartphone usage among individuals with schizophrenia, it has been suggested that symptoms such as paranoia, disorganization, and cognitive impairment may limit the feasibility of technology-based interventions for this patient group.…”
Section: Introductionmentioning
confidence: 99%
“…5 The attitudes adopted by the nurses in relation to the family will determine the care process. 13 Being aware of this need, we developed this way, and, although there are studies conducted into the attitudes towards families in several contexts, 7,14,15 few is directed to the person with mental disorder. 16,17 In the mental health sector, it is important that we involve the families to care to maximize the quality of intervention offered.…”
Section: Introductionmentioning
confidence: 99%